The safety and feasibility of minimal invasive plate osteosynthesis (MIPO) of the posterior aspect of the humerus: A cadaveric study - C. Jiamton (2018)
© 2018 Wiley Periodicals, Inc. The aim of this study was to determine the feasibility of applying MIPO of the humerus via the posterior approach and to observe the tension of the radial nerve in different elbow positions. Two separate incisions were made on the posterior aspect of the humerus in ten fresh cadavers (20 humeri). The radial nerve was identified at the proximal incision and the distances through which the nerve could be elevated from the bone with the elbow in flexion and extension were measured. A 10-hole extra-articular distal humeral locking compression plate was inserted and fixed through the submuscular tunnel. The tunnel was then explored to identify any entrapment of the radial nerve and to observe the anatomical relationship of the radial nerve to the plate and bone. There was no entrapment of the radial nerve or its branches. The distances through which the radial nerve could be elevated were greater with the elbow in extension than in flexion (P < 0.01). The radial nerve crossed the medial and lateral borders of the posterior surface of the humerus at 80.1–132 mm (average 104.7 mm) and 116.6–175.5 mm (average 142.7 mm) of its total length, respectively. The axillary nerve was located at 38.7–61.7 mm (average 47.9 mm) of total humeral length. MIPO of the humerus using the posterior approach is an alternative option for treating distal humeral shaft fracture. The risk of radial nerve injury can be minimized by careful dissection in the proximal incision. Clin. Anat., 2018. © 2018 Wiley Periodicals, Inc.